Penerapan Terapi Musik Terhadap Hemodinamik pada Anak Dengan Leukemia di Ruang Flamboyan 9 RSUD Dr. Moewardi Surakarta - Ellen Putri Liliarmita Khasanah; Irma Mustika Sari; Lin Marhamah Azizah (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Leukemia is a progressive malignant disease of the blood-forming tissues. Leukemia is caused by abnormal growth of white blood cells (leukocytes) in the bone marrow. These cells then spread in the blood circulation. This disease is still a public health problem in the country and in the world, which affects children to adults, leukemia is a cancer with the highest death cases in the world. One of the complementary therapies that can be used to improve the psychological response of cancer patients is music therapy. Music therapy can increase relaxation and reduce anxiety in leukemia patients during the chemotherapy process. Objective : Knowing the results of the application of music therapy to hemodynamics in children with leukemia in the room Flamboyan 9 RSUD Dr. Moewardi surakarta. Method : Methods of data collection in this application is to use the method of interviews, and observation. Findings : After performing music therapy for 1 day, the results were the same for both respondents, that is, children can lower blood pressure and pulse frequency within normal limits. Implication : Music therapy can affect the decrease in hemodynamics in children with leukemia because there are significant changes in hemodynamics from height to decrease.